Report of visitto Harare: 27 April to 15 May 1998 - Valerie Ehlers (AOSIS, 1999)
The World Health Organisation (WHO) and the Commonwealth offered a joint workshop for nurses and midwives from the RSA, Mocambique, Zimbabwe, Zambia and Uganda lasting three weeks. Three nurses from the RSA, namely Mrs Mamorwa Gololo from the South African Municipal Workers' Union, Mrs Elza Lubbe from George Hospital and Dr Valerie Ehlers from Unisa, participated in this workshop in Harare. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.